2012
DOI: 10.1371/journal.pgen.1002669
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Chloroplast RPS1 Negatively Modulates Nuclear Heat-Responsive Expression of HsfA2 and Its Target Genes in Arabidopsis

Abstract: Heat stress commonly leads to inhibition of photosynthesis in higher plants. The transcriptional induction of heat stress-responsive genes represents the first line of inducible defense against imbalances in cellular homeostasis. Although heat stress transcription factor HsfA2 and its downstream target genes are well studied, the regulatory mechanisms by which HsfA2 is activated in response to heat stress remain elusive. Here, we show that chloroplast ribosomal protein S1 (RPS1) is a heat-responsive protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 116 publications
(165 reference statements)
3
122
0
Order By: Relevance
“…In eukaryotes, these are known to be sensed in the cytosol, the endoplasmic reticulum (ER), and mitochondria and signaled to the nucleus to initiate appropriate transcriptional responses (Voellmy and Boellmann, 2007;Walter and Ron, 2011;Haynes et al, 2013). Recent work suggested that an unfolded protein response also exists in the chloroplast (Yu et al, 2012;Schmollinger et al, 2013;Ramundo et al, 2014). Plasma membrane fluidity has been identified as an important temperature sensor in land plants that appears to lie upstream of the unfolded protein response (Sangwan et al, 2002;Suri and Dhindsa, 2008;Saidi et al, 2009;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, these are known to be sensed in the cytosol, the endoplasmic reticulum (ER), and mitochondria and signaled to the nucleus to initiate appropriate transcriptional responses (Voellmy and Boellmann, 2007;Walter and Ron, 2011;Haynes et al, 2013). Recent work suggested that an unfolded protein response also exists in the chloroplast (Yu et al, 2012;Schmollinger et al, 2013;Ramundo et al, 2014). Plasma membrane fluidity has been identified as an important temperature sensor in land plants that appears to lie upstream of the unfolded protein response (Sangwan et al, 2002;Suri and Dhindsa, 2008;Saidi et al, 2009;Wu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…26,29 Analysis of the rps1 mutant demonstrated that the chloroplast ribosomal protein S1 (RPS1) mediates retrograde signaling to modulate the expression of the heat-responsive nuclear transcription factor HsfA2 and its target genes during heat stress, although the specific plastid retrograde signal is unknown. 30 Recently, gene cloning and transcriptional analysis of the Arabidopsis ammonium-overly-sensitive 1 (amos1) that are needed for maintaining the stability of the thylakoid membrane system under normal growth conditions. 30 As an example of the fifth type, PLEIOTROPIC RESPONSE LOCUS 1 (PRL1) protein, located in the nucleus, appears to play a major role in modulating plant responses to environmental changes by interconnecting 1 O 2 -mediated retrograde signaling with energy signaling pathways.…”
Section: Molecular Components In Plastid Retrograde Signaling To Regumentioning
confidence: 99%
“…30 Recently, gene cloning and transcriptional analysis of the Arabidopsis ammonium-overly-sensitive 1 (amos1) that are needed for maintaining the stability of the thylakoid membrane system under normal growth conditions. 30 As an example of the fifth type, PLEIOTROPIC RESPONSE LOCUS 1 (PRL1) protein, located in the nucleus, appears to play a major role in modulating plant responses to environmental changes by interconnecting 1 O 2 -mediated retrograde signaling with energy signaling pathways. 23 The most recently characterized molecular component, EGY1, the first metalloprotease site-2 protease (S2P) homolog discovered in plants and located in plastids, is required for normal chloroplast development such as thylakoid grana stacking, the development of the lamellae system, and the accumulation of chlorophyll and chlorophyll a/b binding proteins.…”
Section: Molecular Components In Plastid Retrograde Signaling To Regumentioning
confidence: 99%
See 2 more Smart Citations